Extracts of red peppers: antioxidant activity and sensory evaluation. Issue 2 (14th March 2016) - Jorge, Neuza; Veronezi, Carolina Médici; Pereira, Danusa Cassiano
Abstract : Purpose: – This study aims to deal with the evaluation of the antioxidant capacity of lyophilized hydroalcoholic extracts of red peppers in natura . Furthermore, preference was evaluated for the taste and color of soybean oil added red pepper extracts. Design/methodology/approach: – The antioxidant capacity was determined by four methods. The content of phenolic compounds, carotenoids and ascorbic acid in the extracts was determined by chromatographic, spectrophotometric and titration methods, respectively. Findings: – The results showed that the highest antioxidant capacity was found in Malagueta pepper extract through reducing power (FRAP) method. In this same extract, high amount of phenolic compounds was found. However, the extracts of Bode and Dedo-de-moça peppers had higher amounts of carotenoids and ascorbic acid, respectively. Sensorially, the oil added extracts were preferred. Practical implications: – Red peppers are very popular and consumed worldwide, besides being constituted of important phytochemicals. Results showed high antioxidant activity in the extracts of peppers, and high content of phenolic compounds, carotenoids and ascorbic acid mainly in chili. This study highlights the importance of the extracts of red peppers, genus Capsicum, as a source of antioxidants, in addition to vegetable oils. Originality/value: – It is important to check the acceptance of the application of extract in vegetable oil, so it can be marketed as a natural antioxidant. This study provides valuable information about the antioxidant capacity of extracts of red peppers and its acceptance.